Application of the lumped parameter line model to simulate electromagnetic transients in three-phase transmission lines with vertical symmetry - Garbelim Pascoalato, Taina Fernanda [UNESP]; Torrez Caballero, Pablo [UNESP]; Kurokawa, Sergio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
In this paper, we propose a transmission line model to represent three-phase untransposed transmission lines with vertical symmetry. Here, we decouple a transmission line into its propagation modes using Concordia's matrix, which is the proper orthogonal form of Clarke's matrix that has its columns normalised. Due to the usage of Concordia's matrix, the transmission line is decoupled into two coupled modes and one uncoupled mode. We represent the uncoupled mode by a single-phase transmission line, and the coupled modes by a two-phase transmission line without vertical symmetry. We compute voltages and currents for the single-phase transmission line using the classic Lumped Parameter Model. Voltages and currents in the two-phase transmission line are calculated using a cascade of coupled L circuits pairs. Modal voltages and currents are then transformed back to the phase domain. We compare the results obtained with the proposed model to those obtained with two well-known time domain models, the classic modal lumped parameter model and the lumped parameter model available in the Alternate Transients Program ATP. Results show that the proposed model agrees with time-domain models and has the advantage that is developed in the time domain without needing any inverse transformations.
Keywords: Electromagnetic transients; lumped parameters; modal decomposition; time domain; transmission lines